AB1407 Musculoskeletal teaching and training in saudi arabia: A national survey. (23rd January 2014) - Zaini, R.; Almoallim, H.; AlRehaily, A.; Samannodi, M.; Bawayan, M.; Hafiz, W.; Attar, D.; Awan, S.; Hafiz, H.
Abstract : Background: Musculoskeletal (MSK) symptoms are the most common reason for patients to seek medical attention, accounting approximately 20% of both Primary care and emergency-room visits. Despite the high prevalence of musculoskeletal disorders in all fields of clinical practice, doctors continue to describe poor confidence in their musculoskeletal clinical skills. Studies report the neglect of musculoskeletal examination skills in clinical practice and insufficient competence to carry out MSK history taking and physical examinations among clinicians. Objectives: The main purpose of the study is to investigate the importance of Musculoskeletal (MSK) medicine in daily practice and the self-confidence to demonstrate MSK clinical skills (history taking and physical examinations) from the prospective of residents of Internal Medicine in Saudi Arabia. The study will also highlight factors that may affect respondents confidence, explore the educational and training opportunities provided in undergraduate and postgraduate programmes and determine possible barrier. Methods: Paper-based, close-ended questionnaire with 5point Likert scale is developed based on intensive literature reviews. The piloted questionnaire consisted of 31 item that focus on four major themes:The study population is Residents of the Internal Medicine in Saudi Arabia. Results: 296 residents of Internal Medicine complete the questionnaire with 42% response rate, representing 21 residency programmes in ten different cities that covering five regions of Saudi Arabia:The study indicate residents' lower confidence in demonstrating MSK Physical Examinations with total mean (10/24). There is a significant difference in residents' perception of their confidence in demonstrating MSK physical examination regarding their gender: Male residents show higher confidence in demonstrating MSK physical exam: in general, of the hips and pelvis, of foot and ankle, and of back. Respondents have general agreement that MSK problems are common in patient visits and indicate the importance of MSK clinical screening in all standard clinical examination of patients, yet they point to current inappropriate practice in handling most cases: Residents indicate their inattention to perform MSK physical examination unless there is a serious complication. Respondents have a lower perception of undergraduate and postgraduate training, regarding the inadequate training and assessment in MSK, and teachers ignorance of MSK training in other departments. In addition, most residents agree that integrated medical training and practice with a constancy of MSK physical examinations training and education are essential to develop graduates and residents skills. Conclusions: The study shows a major threaten in clinical practice: most Internal Medicine residents in the Saudi Arabia have a lower confidence in MSK physical exam. Most medical schools and Internal Medicine residency programmes do not effectively educate future physicians on MSK medicine in spite of the increasing prevalence of MSK conduction across medical practice.An urgent national study must focus on integrating teaching and training with standardised approach and to emphasis rapid MSK clinical screening in all standard clinical examination. Disclosure of Interest: None Declared